Android-Based Electronic Patient Record Implementation Using Software Engineering Principles (International Journal of Engineering and Computer Science, 2024)
An Android-based electronic patient record application is developed. The goal is to emphasize the importance of automating medical and clinical procedures, especially when data collection and management is involved. A secondary goal is to manifest the efficiency of developing an application using software engineering principles. This application shall replace a paper-based patient record, allowing the medical practitioners to create electronic records of patients. Furthermore, it can be a tool to help health care workers in maintaining patients’ information with higher efficiency and security.